Kesetimbangan Adsorpsi Logam Cu Menggunakan Karbon Aktif Dari Ampas Tebu Sebagai Adsorben - Yenti, Silvia Reni; Astrandana, Yudi; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bagasse is a by product of the extraction process (pressing) liquid sugar. One of the efforts to control the bagasse is processed into activated carbon. This research aims to study activated carbon manufacturing process of bagasse, study the effect of Cu concentration and temperature of Cu solution on activated carbon from bagasse as and determine of equilibrium models that used at Cu metal adsorption using activated carbon from bagasse. Processing bagasse into activated carbon carbonization process is carried out at a temperature of 320 ° C for 2 hours. After that is activated using KOH with comparison of activated carbon to KOH 1:3. As much as 1.5 grams of activated carbon was added to the beaker containing the solution of Cu at various concentration (20 ppm, 30 ppm and 40 ppm), the reaction temperature (40 ° C, 50 ° C and 60 ° C) at a volume of 500 ml solutions. The results showed that activated carbon adsorption for is 97.1%, followed equilibrium models Freundlich isotherm models.Keywords: Adsorption, Cu Metal, Carbonization, Activated Carbon